The Split-Brain Phenomenon Revisited: A Single Conscious Agent with Split Perception. Issue 11 (November 2017) - Pinto, Yair; de Haan, Edward H.F; Lamme, Victor A.F.
Abstract : The split-brain phenomenon is caused by the surgical severing of the corpus callosum, the main route of communication between the cerebral hemispheres. The classical view of this syndrome asserts that conscious unity is abolished. The left hemisphere consciously experiences and functions independently of the right hemisphere. This view is a cornerstone of current consciousness research. In this review, we first discuss the evidence for the classical view. We then propose an alternative, the 'conscious unity, split perception' model. This model asserts that a split brain produces one conscious agent who experiences two parallel, unintegrated streams of information. In addition to changing our view of the split-brain phenomenon, this new model also poses a serious challenge for current dominant theories of consciousness. Trends: Five hallmarks characterize the split-brain syndrome: a response × visual field interaction, strong hemispheric specialization, confabulations after left-hand actions, split attention, and the inability to compare stimuli across the midline. These hallmarks underlie the classical notion that split brain implies split consciousness. This notion suggests that massive interhemispheric communication is necessary for conscious unity. Closer examination challenges the classical notion. Either the hallmark also occurs in healthy adults or the hallmark does not hold up for all split-brain patients. A re-evaluation of the split-brain data suggests a new model that might better account for the data. This model asserts that a split-brain patient is one conscious agent with unintegrated visual perception. This new model challenges prominent theories of consciousness, since it implies that massive communication is not needed for conscious unity.